Adaptive assessment tool: Analysis of digital instrument development needs to measure critical thinking skills in static fluid materials - Novela, Erma; Viyanti, Viyanti; Rohman, Fatkhur (Indonesian Journal of Science and Mathematics Education, 2025)
21st-century education emphasizes critical thinking as a core competency that must be developed in learning, including physics. However, teacher assessments are still based mainly on conventional written exams, limiting the comprehensive measurement of students’ critical thinking skills. This issue is critical, especially for complex topics such as static fluids. This study aims to analyze the need for developing adaptive assessment-based instruments in physics learning. A descriptive approach was used, with data collected via questionnaires from 24 physics teachers and 37 high school students in Lampung Province. Data were analyzed using percentages for closed-ended questions and descriptive narratives for open-ended responses. Results indicate that physics assessments remain dominated by written tests, critical thinking indicators are incompletely measured, and question quality is rarely analyzed in depth. Although teachers and students have used digital assessments, these are not adaptive, as all students receive questions at the same difficulty level. The implications highlight the importance of developing valid, reliable, and practical adaptive assessment instruments that can adjust to students’ abilities. Such instruments can improve the measurement of critical thinking, support more effective and personalized learning, and strengthen both the theoretical understanding and practical application of adaptive assessment in physics education.